Implementasi Pendekatan ABCD dalam Metode Hafalan Kitab Mutamimah Untuk Penguatan Ilmu Nahwu di Pondok Pesantren Nurul Qur’an Ponorogo 2025 - Latifatum Muthoharoh; Ahmad Kirom (Social Science Academic, 2025)
This article discusses the Implementation of the ABCD Approach in the Book of Mutamimah Memorization Method to strengthen nahwu knowledge at the Nurul Qur'an Islamic Boarding School in Ponorogo. This service article aims to identify supporting and inhibiting factors in the process of memorizing the book of mutamimah at the Nurul Qur'an Islamic Boarding School in Ponorogo, as well as analyzing memorization-based nahwu learning strategies. The ABCD approach emphasizes the use of the potential, assets, and strengths possessed by students and the pesantren environment, so that the learning process does not only focus on weaknesses, but on the development of existing abilities. The subjects of this research include students, and education administrators. This research was conducted on July 20-August 25, 2025 at the Nurul Qur'an Islamic Boarding School. In the practical process, students are required to make memorization deposits to listeners every day. Some students were able to complete memorization to khatam within six months. The process of strengthening nahwu knowledge at the Nurul Qur'an Islamic Boarding School in Ponorogo is carried out through several methods, including tikrar (repetition), memorization deposit of the book of mutamimah, and muroja'ah.